An Overview of Spinal Injuries due to Dive or Fall into Shallow Water: Our Long-Term, Double-Center Experience from the Aegean Coast - Murat Yılmaz; Ersin Ikizoglu; Mert Arslan; Erkin Ozgiray; Kadri Emre Calıskan; Resat Serhat Erbayraktar (Emergency Medicine International)
Purpose. We aimed to evaluate the demographic and clinical features of patients with cervical spinal injuries secondary to shallow-water diving and share our therapeutic outcomes. Methods. A retrospective study was carried out using data extracted from the medical files of 39 patients (3 females and 36 males) who were treated surgically (n = 29) or conservatively (n = 10). Demographics, clinical features, operative data, American Spine Injury Association (ASIA) impairment scales, and Karnofsky Performance Status (KPS) results were noted. Results. The average age of our series (n = 39) was 31.59 ± 14.80 (range, 14 to 92) years. The vast majority of patients (n = 34, 87.2%) presented with isolated cervical trauma. At initial admission, neurological deficits were diagnosed in 22 (56.4%) patients. A single-level cervical involvement was noted in 18 (46.2%) patients, while 21 cases (53.8%) displayed injury involving multiple levels. The levels of cervical injury were C5 (n = 16, 41%), C6 (n = 11, 28.2%), C7 (n = 6, 15.4%), C1 (n = 5, 12.8%), and C4 (n = 1, 2.6%). A total of 22 patients had neurological deficits at admission. Surgery was performed using anterior (n = 21, 72.4%), posterior (n = 7, 24.1%), and combined anterior and posterior (n = 1, 3.4%) routes. Nine patients (23.1%) exhibited improvement in their neurological deficits. There were significant improvements in both the ASIA impairment scale and KPS results after treatment. Conclusion. Our data indicated that dive- or fall-related cervical spinal injuries are associated with profound morbidity. Reinforcement of primary prevention, identification of target population, and increased awareness on this topic are the key steps to minimize the frequency and severity of complications and to optimize therapeutic outcomes.